2014
DOI: 10.1038/npjpcrm.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of the use of domiciliary intravenous antibiotics in bronchiectasis

Abstract: Background:We introduced domiciliary intravenous (IV) antibiotic therapy in patients with bronchiectasis to promote patient-centred domiciliary treatment instead of hospital inpatient treatment.Aim:To assess the efficacy and safety of domiciliary IV antibiotic therapy in patients with non-cystic fibrosis bronchiectasis.Methods:In this prospective study conducted over 5 years, we assessed patients’ eligibility for receiving domiciliary treatment. All patients received 14 days of IV antibiotic therapy and were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…A lower percentage of patients undergoing high-resolution CT scan and standard testing for bronchiectasis aetiology is reported in the present SIP audit in comparison to the 2012 UK audit [6]. Five more areas require particular attention, including: monitoring sputum bacteriology; promoting airway clearance taught by a specialist respiratory physiotherapist and pulmonary rehabilitation in selected patients; and developing services to allow domiciliary intravenous antibiotic treatment [12]. Possible reasons for low adherence to the quality standards include the absence of Italian and European guidelines, and lack of awareness of the disease and of the evidence base to support recommendations.…”
Section: To the Editormentioning
confidence: 91%
“…A lower percentage of patients undergoing high-resolution CT scan and standard testing for bronchiectasis aetiology is reported in the present SIP audit in comparison to the 2012 UK audit [6]. Five more areas require particular attention, including: monitoring sputum bacteriology; promoting airway clearance taught by a specialist respiratory physiotherapist and pulmonary rehabilitation in selected patients; and developing services to allow domiciliary intravenous antibiotic treatment [12]. Possible reasons for low adherence to the quality standards include the absence of Italian and European guidelines, and lack of awareness of the disease and of the evidence base to support recommendations.…”
Section: To the Editormentioning
confidence: 91%
“…One study looking at outpatient attendance 22 did find a higher death rate (1 patient vs. 0 patients), but this was a small study and the overall rate of side effects was lower in OPAT patients (15% vs. 18%). There also appears to be no conclusive evidence of benefit either in relation to hospital readmissions overall, or in relation to those who self-administered therapy, 42,59 although there were conflicting results for OPAT provided by nurses, with SNs 10,25,57,64 seemingly having superior results to those of GNs. 12,41 Perhaps unsurprisingly, overall there would appear to be more line-related complications in i.v.…”
Section: Patient Safety and Adverse Eventsmentioning
confidence: 93%
“…When all models are considered, OPAT appears to produce superior results compared with inpatient treatment, a finding that is influenced by the inclusion of positive studies reporting on multiple or unspecified OPAT treatment models. When these studies are removed and specific models are considered individually, outpatient attendance appears to have a lower rate of cure or improvement, 22 and SA 59 or OPAT by a SN has a higher rate, 56,57 whereas OPAT by GN has no impact. 12,41 Results from those studies assessing the impact of treatment via OPAT specifically on lung function in patients with cystic fibrosis were either inconclusive or found no impact.…”
Section: Impact On Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…This might then provide a basis upon which tailored interventions can be tested to not only improve bronchiectasis care but simultaneously reduce healthcare costs. As an example, Bedi et al [7] investigated home intravenous antibiotic treat-DOI: 10.1159/000490550 ment in bronchiectasis patients. They showed that this intervention was safe, resulted in less morbidity, was as efficient as hospital-based treatment, and reduced the hospitalization days significantly, thus the healthcare costs.…”
mentioning
confidence: 99%